2006
DOI: 10.1097/01.prs.0000239450.92690.72
|View full text |Cite
|
Sign up to set email alerts
|

Defining Vascular Supply and Territory of Thinned Perforator Flaps: Part II. Superior Gluteal Artery Perforator Flap

Abstract: The superior gluteal artery perforator flap provides an excellent blood supply to adipose tissue but may be compromised when aggressively thinned. Surgeons may design and harvest partially thinned superior gluteal artery perforator flaps based on the anatomical vascular territory maps provided by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…In a majority of cadavers, the SG had a normal course and is similar to previous reports in Caucasian [8] and Thai populations. However, variations were seen in the SG, wherein one cadaver (1.61%) it provided origin to the OA, while in another cadaver (1.61%), the SG and IG originated as a common trunk along with the LS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In a majority of cadavers, the SG had a normal course and is similar to previous reports in Caucasian [8] and Thai populations. However, variations were seen in the SG, wherein one cadaver (1.61%) it provided origin to the OA, while in another cadaver (1.61%), the SG and IG originated as a common trunk along with the LS.…”
Section: Discussionsupporting
confidence: 88%
“…The mean external diameter of SG was 1.26 ± 0.22 mm on the left side and 1.28 ± 0.21 mm on the right side. The length of the SG in this study is comparable to previous values in Caucasian 8 populations where the reported lengths were 5.7-6.6 cm , 3.99-4.01 cm 9 and 4.09-4.67 cm . However, they were not comparable to a Thai population of 6.44-7.33 cm.…”
Section: Discussionsupporting
confidence: 88%
“…They showed that although the SGAPs supplied the upper gluteal region and the IGAPs the lower gluteal region, the central portion was a variable region, with dominance of either the SGA or the IGA dictating the source pedicle for perforators in this region. [19,[21][22][23], whereas the average number of inferior gluteal perforators varies from 8 to 9 [19,21].…”
Section: Flap Design and Blood Supplymentioning
confidence: 99%
“…A gluteal augmentation flap [14], supplied by perforators from the superior gluteal artery, lateral sacral arteries, and lumbar artery [14,20,33], can be added to correct insufficient buttock projection. Colwell [36] showed that major perforators are generally situated 6-9 cm from the midline, whereas Nojima [63] placed them 10-12 cm from the midline. Despite the effect on gluteal projection, these techniques may actually increase the complication rate [43].…”
Section: Current Trends In Techniquementioning
confidence: 99%